Financial Development, ICT Use, Renewable Energy Consumption and Foreign Direct Investment Impacts on Environmental Degradation in OIC Countries - Iram, Maria; Zameer, Sahrish; Asghar, Muhammad Muzammil; Kalsoom, Umm-e- (Pakistan Journal of Humanities and Social Sciences, 2024)
This article examines the influence of financial development, ICT use, FDI and renewable energy on environmental degradation in 38 OIC countries using panel data from 2003 to 2021. For data estimation, the authors employed the CD test, slope homogeneity test, CIPS and CADF test, FGLS model, PCSE model and Dumitrescu Hurlin panel causality test. It is found that the variables have cross-sectional dependence, slope heterogeneity, heteroskedasticity, and autocorrelation in a model. The Westerlund test of cointegration also ensures the cointegration among variables in a model while panel unit root tests found the mixed integration order of variables. The FGLS model shows that FD and renewable energy consumption negatively and significantly influence CO2 emissions in OIC countries. The outcomes also show that the use of ICT and FDI inflows in OIC countries are positively related to CO2 emissions. The PCSEs model is used as a robustness estimation technique which also confirms the estimates of the FGLS model. The authors suggested that financial development should be promoted to finance green energy projects, design regulatory policies to prevent polluted technology from the FDI inflows and to prevent the harmful effects of ICT on the environment, the use of green energy resources in ICT use should be promoted.